An application to support COVID-19 occupational health and patient tracking at a Veterans Affairs medical center. (17th October 2020) - Fillmore, Nathanael R; Elbers, Danne C; La, Jennifer; Feldman, Theodore C; Sung, Feng-Chi; Hall, Robert B; Nguyen, Vinh; Link, Nicholas; Zwolinski, Robert; Dipietro, Svitlana; Miller, Stephen J; Aleksanyan, Anahit; et al.
Abstract: Objective: Reducing risk of coronavirus disease 2019 (COVID-19) infection among healthcare personnel requires a robust occupational health response involving multiple disciplines. We describe a flexible informatics solution to enable such coordination, and we make it available as open-source software. Materials and Methods: We developed a stand-alone application that integrates data from several sources, including electronic health record data and data captured outside the electronic health record. Results: The application facilitates workflows from different hospital departments, including Occupational Health and Infection Control, and has been used extensively. As of June 2020, 4629 employees and 7768 patients and have been added for tracking by the application, and the application has been accessed over 46 000 times. Discussion: Data captured by the application provides both a historical and real-time view into the operational impact of COVID-19 within the hospital, enabling aggregate and patient-level reporting to support identification of new cases, contact tracing, outbreak investigations, and employee workforce management. Conclusions: We have developed an open-source application that facilitates communication and workflow across multiple disciplines to manage hospital employees impacted by the COVID-19 pandemic.